Vanity, vitality, and virility : the science behind the products you love to buy - Emsley, John (Oxford University Press, 2004)
The science behind alpha-hydroxy acids, chlorine bleach, and other chemicals that people use every day is explored in a fascinating study that examines, through amusing anecdotes and odd facts, if and how they work. What is the secret of shower cleaners? How does the dangerous explosive nitroglycerin ward off heart attacks? And what medicines, usually prescribed for other purposes, are said to produce the ultimate orgasm? In Vanity, Vitality, and Virility, award-winning science writer John Emsley offers a fascinating behind-the-scenes account of 30 chemicals that we use everyday to make ourselves more beautiful, to improve our diet and sexual pleasure, to kill germs, and to ward off depression and other mental illnesses. Emsley looks at common compounds such as alpha-hydroxy acids, vitamin C, chlorine bleach, and Prozac, telling us if they work, how they work, and how they were discovered. Indeed, the book is packed with useful information and easy-to-digest science, and Emsley relates it all with a light touch that delights in the odd fact or amusing anecdote. Thus we learn of the "vitamin C tights" sold in Japan to make your legs more beautiful (they don't work) and of the whimsical Hungarian scientist who first isolated vitamin C and wanted to name it "godnose", because he had no idea what the compound was. We discover that Cleopatra was right to bath in milk, which is filled with alpha-hydroxy acids. And we read about the unforgettable British researcher who demonstrated a powerful new drug for male erections at a Las Vegas convention, injecting himself with the compound and then "displaying the results" to a stunned lecture hall. As with the much-loved Nature's Building Blocks, in John Emsley's hands, chemistry comes alive. Anyone curious about the ingredients in the products we use, and everyone fascinated with science, will be enthralled by this book.